Business Strategy Development Pharmacy Canvas Model Based Medical Vehicle for Increase Trust Consumers and Turnover Sale - Sri Rachmi Firdausi (Jurnal Info Sains : Informatika dan Sains, 2023)
The Covid 19 pandemic has had a major impact on global businesses, especially the pharmaceutical business. Wahana Medika Bekasi Pharmacy has experienced a significant decrease in turnover since the pandemic. Tight competition and pandemic conditions have contributed to the decline in turnover. One of the factors that needs to be studied is the business strategy applied that relevant solutions can be found to increase turnover. This study aims to analyze the right business strategy using the Business Model Canvas approach and SWOT analysis. Data collection was carried out by survey and in-depth interviews. Respondents consisted of 80 customers and 40 non-customers, 20 pharmacists, and 12 informants consisting of pharmacy owners and pharmacists. Data analysis used SWOT analysis with 9 BMC element mapping. The results showed that there were 6 elements of BMC found in the business strategy applied by the Wahana Medika Bekasi Pharmacy during the period, namely: customer segmentation, channels, customer relations, value proposition, key activities, and cost structure. The obstacles experienced in increasing turnover are customer data that has not been specifically segmented, low brand awareness, and less innovative promotion. A new business strategy is recommended by implementing 3 new elements, namely Key Partnership, Key Resources, and Revenue Stream. It is recommended that the business strategy with 9 BMC elements be used as an action plan in company managerial and conducted periodic evaluations. It is necessary to develop human resources and the application of information technology to optimize sales and promotions.